Do Clients Get What They Pay For? Evidence from Auditor and Engagement Fee Premiums - Moon, James R.; Shipman, Jonathan E.; Swanquist, Quinn T.; Whited, Robert L. (Contemporary Accounting Research, 2019)
ABSTRACT Despite the intuitive appeal, prior research finds mixed evidence on whether higher audit fees translate to superior audit quality. Under the assumption that product differentiation between auditors is based, in large part, on the level of financial statement assurance, we propose more refined measures of excess audit fees that separate auditor premiums from other fee premiums. Consistent with our conjecture, we identify significant variation in audit pricing across auditors (i.e., auditor premiums) that relates positively to audit quality. Conversely, we find no evidence that higher engagement‐specific fee premiums (i.e., fee model residuals) are positively related to proxies for audit quality. Additional tests indicate that our results do not simply reflect premiums attributable to auditor characteristics evaluated in prior research (e.g., Big 4 membership, office size, and industry expertise). In fact, our findings suggest that the positive association between auditor premiums and audit quality is better captured at the auditor level than it is at the auditor “tier,” office, auditor‐industry, or engagement levels. In sum, our results suggest that auditors charging higher fees, on average, deliver superior levels of financial statement assurance, but engagement‐specific fee premiums do not reflect quality‐enhancing audit effort. These contrasting results provide a possible explanation for the mixed findings in prior research.